Death, Life, and Resurrection: Christology, Ethics, and Soteriology in Romans 6,1-14 - Christos Karakolis (Dying with Christ – New Life in Hope: Romans 5,12–8,39, 2021)
Romans 6,1-14 is central to Pauline thought, both in the letter to the Romans and in the Apostle’s theology as a whole, and this is the reason for its multifaceted history of interpretation, influence, and reception. While this text has many interpretative and hermeneutical dimensions, in this essay we will select an exegetical approach, with emphasis on the detailed examination of its structure, flow, terminology, and theo- logical content. Due to its particular theme, we will mainly focus on the interplay between the terms and theological ideas relating to the concepts of death, life, and resurrection, while also linking christology, ethics, and soteriology to each other.